2021
DOI: 10.1111/epi.16911
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study of epilepsy in a Japanese population identified an associated region at chromosome 12q24

Abstract: Objective: Although a number of genes responsible for epilepsy have been identified through Mendelian genetic approaches, and genome-wide association studies (GWASs) have implicated several susceptibility loci, the role of ethnic-specific markers remains to be fully explored. We aimed to identify novel genetic associations with epilepsy in a Japanese population. Methods: We conducted a GWAS on 1825 patients with a variety of epilepsies and 7975 control individuals. Expression quantitative trait locus (eQTL) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Therefore, the CUX2 recurrent variant in EEs may not be enough to explain the genome-wide association with epilepsy at the 12q24 region in Japanese population. In our GWAS study 5 , sub-analyses for subtypes of epilepsies further revealed that a polymorphic marker at the 12q24 epilepsy-associated region showed genome-wide significant association with structural/metabolic epilepsy. Hippocampal sclerosis is the major entity for structural/metabolic epilepsy, and therefore the CUX2 variants in patients with TLE would contribute to the association with epilepsy at 12q24 in Japanese population.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Therefore, the CUX2 recurrent variant in EEs may not be enough to explain the genome-wide association with epilepsy at the 12q24 region in Japanese population. In our GWAS study 5 , sub-analyses for subtypes of epilepsies further revealed that a polymorphic marker at the 12q24 epilepsy-associated region showed genome-wide significant association with structural/metabolic epilepsy. Hippocampal sclerosis is the major entity for structural/metabolic epilepsy, and therefore the CUX2 variants in patients with TLE would contribute to the association with epilepsy at 12q24 in Japanese population.…”
Section: Discussionmentioning
confidence: 68%
“…All of these patients with CUX family variants showed symptoms of epileptic seizures, suggesting that the variants may contribute to the threshold for the triggering epileptic seizures through a facilitation of excitatory synaptic transmission from entorhinal cortex to hippocampus in epilepsies caused by CUX family variants. Our recent GWAS analysis of Japanese patients with variable epilepsies identified a region with genome-wide significance at chromosome 12q24 which harbors CUX2 5 . Although a recurrent de novo CUX2 variant p.E590K has been described in patients with EEs 6 , 7 , a previous whole exome sequencing study for Japanese patients with EEs 17 did not find the CUX2 pathogenic variant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CUX2 controls neuronal proliferation, dendrite branching, spine morphology and synapse formation 3,4 . We recently reported a genome-wide association study (GWAS) on 1,825 Japanese patients with variable epilepsies which identified an associated region at chromosome 12q24.11 – 12q24.13 harboring 24 transcripts including CUX2 gene 5 . In the region, CUX2 is only gene which has been reported to be relevant for epilepsy; a recurrent de novo variant (c.1768G>A, p.E590K) has been identified in patients with rare epileptic encephalopathies (EEs) 6,7 .…”
Section: Introductionmentioning
confidence: 99%